Trends and Challenges Industry Halal Cosmetics: Opportunities Growth in Indonesia and Global Markets - Khoiriyah, Eva Zunia; Wulan Dari, Azizah; Novelika, Lutfiyah Rahma; Fahrullah, A'rasy (Journal Creative Economics and Trading Halal Ecosystem, 2024)
This research analyze request product halal cosmetics in Indonesia, which is a country with the largest Muslim population in the world. This study use method study library For dig trend, factor drivers, as well as challenges faced by the industry halal cosmetics. Research results show that request to halal cosmetics driven by religiosity consumers, safety and health products, social media influence, and competitive pricing and availability. Generation​ millennials and Gen Z become segment the main determining factor market direction, with preferences influenced by digital promotions. Although regulation like Constitution Guarantee Halal products have give certainty law, challenges such as complex certification processes and lack of education consumer Still become constraints. This study emphasize importance innovation, marketing strategy based on social media, as well as strengthening education and literacy consumer For support growth industry halal cosmetics in Indonesia sustainable